Effect of lattice‐matched InAlGaN electron‐blocking layer on hole transport and distribution in InGaN/GaN multiple quantum wells of visible light‐emitting diodes. Issue 5 (22nd December 2015) - Kim, Jeomoh; Ji, Mi‐Hee; Detchprohm, Theeradetch; Dupuis, Russell D.; Shervin, Shahab; Ryou, Jae‐Hyun
Abstract : We report on the influence of lattice‐matched InAlGaN quaternary electron‐blocking layer (Q‐EBL) on hole transport and distribution in InGaN/GaN multiple quantum wells (MQWs) of visible light‐emitting diodes (LEDs). Triple‐wavelength (TW)‐emitting active region was introduced to deduce carrier transport and distribution from emission intensities of different QWs in TW‐LEDs. The electro‐optical characteristics of TW‐LEDs were compared with respect to the Q‐EBL and silicon doping in a selected QW barrier. In addition, the efficiency droop characteristics of TW‐LEDs according to existence of the Q‐EBL were also investigated. The results show that holes were preferentially injected into a QW adjacent to a p‐type layer in the TW‐LED without the Q‐EBL, while enhanced hole transport to lower QWs closed to an n‐type layer and following uniform distribution were observed in the TW‐LED with the Q‐EBL. The modified kinetic energy of holes overcoming the Q‐EBL is responsible for the improved hole transport and changes in the carrier capturing efficiency of each different QW, resulting in the improved peak efficiency and the efficiency droop of TW‐LEDs.